Regulation of idiopathic pulmonary fibrosis: a cross-talk between TGF-β signaling and MicroRNAs - Wang, Shuo; Yu, Hanming; Liu, Shi; Liu, Yuqing; Gu, Xiu (Frontiers in Medicine, 2024)
Pulmonary fibrosis (PF) is a highly complex and challenging disease affecting the respiratory system. Patients with PF usually have an abbreviated survival period and a consequential high mortality rate after the diagnosis is confirmed, posing serious threats to human health. In clinical practice, PF is typically treated by antifibrotic agents, such as Pirfenidone and Nintedanib. However, these agents have been reported to correlate with substantial adverse effects, escalating costs, and insufficient efficacy. Moreover, it remains unclarified about the multifactorial pathology of PF. Therefore, there is an urgent demand for elucidating these underlying mechanisms and identifying safe, efficient, and targeted therapeutic strategies for PF treatment. The crucial role of the transforming growth factor-β (TGF-β) signaling pathway in PF development has been explored in many studies. MicroRNAs (miRNAs), which function as post-transcriptional regulators of gene expression, can significantly affect the development of PF by modulating TGF-β signaling. In turn, TGF-β signaling can regulate the expression and biogenesis of miRNAs, thereby substantially affecting the progression of PF. Hence, the therapeutic strategies that focus on the drug-targeted regulation of miRNAs, either by augmenting down-regulated miRNAs or inhibiting overexpressed miRNAs, may hinder the pathways related to TGF-β signaling. These strategies may contribute to the prevention and suppression of PF progression and may provide novel insights into the treatment of this disease.